FUZZY LOGIC APPROACH TO ENERGY PLANNING IN NIGERIA - ADE-IKUESAN OLANIKE OLUFISAYO; ATILOLA MORUFDEEN OLATUNBOSUN; OYEDEJI AJIBOLA OLUWAFEMI; ADEYEMI HEZEKIAH OLUWOLE (Journal of Engineering Studies and Research)
Energy planning is an important tool for power system utility company and consumer’s profitability and satisfaction respectively. This paper is a study of energy planning (forecasting) in Ogun state of Nigeria using Fuzzy Logic model. Population and gross domestic product (GDP) are used as the independent variables to forecast load demand based on the previous load demand. After arranging the variables into 5 membership functions and the 19 rules were created, the fuzzy logic model forecast the annual load demand for the next 10 years with a percentage error margin 0.95 % to 21.79 % which results to a mean absolute percentage error (MAPE) of 8.34 %. The result of the forecast shows that within the next 10 years, 2019 to 2028, an average power load of 1985.66 MWH will be required.